Characterization of a Local Renin-Angiotensin System in Rat Gingival Tissue - Santos, C. F.; Akashi, A. E.; Dionisio, T. J.; Sipert, C. R.; Didier, D. N.; Greene, A. S.; Oliveira, Sandra Helena Penha de [UNESP]; Pereira, H. J. V.; Becari, C.; Oliveira, E. B.; Salgado, M. C. O. (Amer Acad Periodontology, 2009)
Background: The systemic renin-angiotensin system (RAS) promotes the plasmatic production of angiotensin (Ang) II, which acts through interaction with specific receptors. There is growing evidence that local systems in various tissues and organs are capable of generating angiotensins independently of circulating RAS. The aims of this study were to investigate the expression and localization of RAS components in rat gingival tissue and evaluate the in vitro production of Ang II and other peptides catalyzed by rat gingival tissue homogenates incubated with different Ang II precursors.Methods: Reverse transcription - polymerase chain reaction assessed mRNA expression. Immunohistochemical analysis aimed to detect and localize renin. A standardized fluorimetric method with tripeptide hippuryl-histidyl-leucine was used to measure tissue angiotensin-converting enzyme (ACE) activity, whereas high performance liquid chromatography showed products formed after the incubation of tissue homogenates with Ang I or tetradecapeptide renin substrate (TDP).Results: mRNA for renin, angiotensinogen, ACE, and Ang II receptors (AT(1a), AT(1b), and AT(2)) was detected in gingival tissue; cultured gingival fibroblasts expressed renin, angiotensinogen, and AT(1a) receptor. Renin was present in the vascular endothelium and was intensely expressed in the epithelial basal layer of periodontally affected gingival tissue. ACE activity was detected (4.95 +/- 0.89 nmol histidyl-leucine/g/minute). When Ang I was used as substrate, Ang 1-9 (0.576 +/- 0.128 nmol/mg/minute), Ang II (0.066 +/- 0.008 nmol/mg/minute), and Ang 1-7 (0.111 +/- 0.017 nmol/mg/minute) were formed, whereas these same peptides (0.139 +/- 0.031, 0.206 +/- 0.046, and 0.039 +/- 0.007 nmol/mg/minute, respectively) and Ang 1 (0.973 +/- 0.139 nmol/mg/minute) were formed when TDP was the substrate.Conclusion: Local RAS exists in rat gingival tissue and is capable of generating Ang II and other vasoactive peptides in vitro. J Periodontol 2009;80:130-139.
Keywords: Angiotensin; gingiva; fibroblasts; renin-angiotensin system; tissue